Digest: Linking coordinated shifts in plant resource allocation to a chromosomal inversion*. (25th April 2019) - Dodsworth, Steven; Pérez‐Escobar, Oscar A.
Abstract: Local adaptation in plants often requires coordinated shifts among resources. Lowry et al. provide evidence for physiological and genomic mechanisms underpinning adaptive shifts in yellow monkeyflower ( Mimulus guttatus), such as the transition between annual and perennial life histories. In M. guttatus, differential activity of gibberellins, governed partially by a chromosomal inversion, is responsible for shifts between growth, reproduction, and herbivore defense (secondary compound production).